Micro Plastic Deformation Behavior of Carbide-Free Bainitic Steel during Tensile Deformation Process - Zhang, Ming (Materials (Basel), 2020)
The microstructure of carbide-free bainitic steel has been widely reported because of its excellent mechanical properties. However, no work has explored the deformation behavior of each phase in the microstructure, namely, retained austenite (RA) and bainitic ferrite (BF). In this paper, the deformation behavior of RA and BF during tension was investigated through the in situ electron backscatter diffusion method. The results showed that the RA surrounded by BF with a high Schmid factor (SF) was accelerated towards being transformed into martensite, but the surrounding BF with low SF value retarded the transformation. The kernel average misorientation (KAM) findings revealed that the strain of the RA and BF rapidly increased initially, slowed down after the critical points of 0.25 and 0.54, respectively, and then increased again. The calculated result for the KAM fraction indicated that the contribution of RA to the total plastic deformation gradually decreased throughout the total tensile process, whereas that of BF increased in the presence of RA.